The Correlation of Anxiety and Behavior of Preventing the Transmission of the Covid-19 Virus in Pregnant Women - Ratih Mega Septiasari; Nurya Viandika (Journal of Ners and Midwifery, 2022)
Indonesia is being the COVID-19 pandemic, where the number of patient deaths has increased. Some reports mention side effects on the fetus in the form of preterm delivery, fetal distress but there is no evidence that COVID-19 infection can pass the transplacental route to the baby. The purpose of this study was to determine the correlation between the level of anxiety and the behavior of preventing transmission of the Covid-19 virus in pregnant women at the Jaya Kusuma Husada Clinic, Kepanjen Malang. This study used descriptive-analytic research with a cross-sectional study design. The population was pregnant women at the Jaya Kusuma Husada Clinic, Kepanjen on January 2021 with a sample of pregnant women using purposive sampling technique with a total of 53 pregnant women as respondents. The independent variable in this study was anxiety. The dependent variable in this study was the behavior of preventing the transmission of the Covid-19 virus. Data collection techniques using a questionnaire. The results of the Spearman Rank statistical test obtained a p-value of 0.090 (sig< 0.050), which meant that there was a negative correlation between the level of anxiety and the health behavior of pregnant women in the COVID-19 pandemic. The COVID-19 pandemic has caused increased anxiety among pregnant women. Anxiety about the risk of contracting COVID-19 encourages pregnant women to take steps to prevent transmission of COVID-19. Pregnant women and the public are expected to follow health protocols to prevent the transmission of COVID-19 for themselves, their families and the surrounding community.